Raising rivals' costs through buyer power - Markus Dertwinkel-Kalt; Justus Haucap; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We re-examine the view that a ban on price discrimination in input markets is particularly desirable in the presence of buyer power. This argument crucially depends on an inverse relationship between downstream firms' profits and the uniform input price. Assuming different input efficiencies among downstream firms, we derive a necessary and sufficient condition such that a higher input price benefits a subset of relatively efficient downstream firms. In such instances, consumers may be better off if discriminatory pricing is feasible.
Keywords: L13; D43; K31; 330; Price discrimination; Buyer Power; Raising Rivals' Costs